2010
DOI: 10.1093/hmg/ddq400
|View full text |Cite
|
Sign up to set email alerts
|

Small insertions and deletions (INDELs) in human genomes

Abstract: In this review, we focus on progress that has been made with detecting small insertions and deletions (INDELs) in human genomes. Over the past decade, several million small INDELs have been discovered in human populations and personal genomes. The amount of genetic variation that is caused by these small INDELs is substantial. The number of INDELs in human genomes is second only to the number of single nucleotide polymorphisms (SNPs), and, in terms of base pairs of variation, INDELs cause similar levels of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
235
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(245 citation statements)
references
References 42 publications
4
235
0
6
Order By: Relevance
“…Indel variation is common even within a single species (Mullaney et al, 2010) and thus it should be no surprise that restriction site associated libraries often sample regions containing such variation. Within repetitive DNA elements (i.e., simple sequence repeats, microsatellites) indels can arise rapidly through slipped-strand mispairing during DNA replication (Levinson and Gutman, 1987), giving rise to single or often tandem repeat nucleotide differences between taxa.…”
Section: Radseq At the Phylogenetic Scalementioning
confidence: 99%
“…Indel variation is common even within a single species (Mullaney et al, 2010) and thus it should be no surprise that restriction site associated libraries often sample regions containing such variation. Within repetitive DNA elements (i.e., simple sequence repeats, microsatellites) indels can arise rapidly through slipped-strand mispairing during DNA replication (Levinson and Gutman, 1987), giving rise to single or often tandem repeat nucleotide differences between taxa.…”
Section: Radseq At the Phylogenetic Scalementioning
confidence: 99%
“…Most indels range between 2-16 bases in length (Mullaney, et al,2010) (also referred to as micro-indels) and their frequency has been shown to vary across the genome with lower rate in conserved and functional regions and an increased rate in hot spots for genetic variation. The average indel rate is approximately one indel in 5.1 to 13.2 kb of DNA (Mills et al, 2006).…”
Section: Insertions and Deletions (Indels)mentioning
confidence: 99%
“…Increasing the read length has also been shown to improve micro-indel (<10 bases) detection sensitivity without significantly affecting specificity, demonstrating a more efficient method for increasing coverage than simply producing more reads. Paired-end reads -Indel detection greatly improves when based on paired end reads deep sequencing data (Mullaney et al, 2010). Both alignment (Li and Durbin, 2009; and variant detection tools (Kai Ye et al, 2009) utilize paired-end reads so that one of the reads is used to pinpoint the pair's loci in the reference while the other read can be subjected to gapped alignment and indel inference.…”
Section: Insertions and Deletions (Indels)mentioning
confidence: 99%
“…Polymorphisms in mature and/or pre-miR sequences may affect miR biogenesis and be associated with the development of various types of cancer (17)(18)(19)(20)(21). Small insertions and deletion (indels) polymorphisms are one of the most common genetic alterations in the human genome that influence human traits and diseases (22,23). There is limited information regarding the association between pre-miR-3131 polymorphisms and cancer risk.…”
Section: Introductionmentioning
confidence: 99%